Factors Affecting Organizational Commitment in Catering Industry: Haidilao as a Case Study - Cao, Feng; Deeprasert, Jirawan (Journal of Ecohumanism, 2024)
Organizational commitment is crucial for organizational development. This study analyzes the case of Hai Di Lao to explore the factors influencing organizational commitment in the restaurant industry. The research methodology includes an online survey, yielding 418 valid responses. The results indicate that both results orientation and employee orientation significantly impact organizational commitment through mediating variables: career goal progress, career competence development, promotion rate, and salary growth. Specifically, results orientation significantly affects career goal progress, career competence development, promotion rate, and salary growth, while employee orientation also significantly influences these career-related outcomes. This study emphasizes the critical role of career competence development, promotion opportunities, and salary growth in enhancing employee loyalty, providing empirical evidence for HR managers and organizational leaders in the restaurant industry to design effective retention strategies. Additionally, it recommends that future research adopt longitudinal methods to explore other potential mediating variables, such as job satisfaction and work-life balance, on organizational commitment.